2021
DOI: 10.3765/elm.1.4871
|View full text |Cite
|
Sign up to set email alerts
|

(Not) acquiring meaning in a second language: Are input deficits key?

Abstract: Word meanings are not always parallel across languages, and second language (L2) learners often use words in non-native ways. Is the learning problem inherent in maintaining conflicting word-to-meaning mappings within an integrated lexical network, or is it due to insufficient attention to and input for acquiring L2 mappings? To help discriminate between these possibilities, we gave English speakers repeated exposures to 40 brief videos of actions, labeled with five novel words that cross-cut English labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…But with collaborators Ping Li and Aneta Pavlenko, we found that even with later second‐language learning, first‐language word use can be influenced by the second language (Malt & Lebkuecher, 2017; Malt, Li, Pavlenko, Zhu, & Ameel, 2015; Pavlenko & Malt, 2011). A number of variables influence where the two languages interact and what the outcomes are (e.g., Malt, 2019c; Malt, Yang, & Joseph, 2021; Pavlenko & Malt, 2011; Zinszer, Malt, Ameel, & Li, 2014). The findings underscore the dynamic nature of the lexical networks, adding to a growing understanding of the flexibility of language representations extending well beyond the early learning years.…”
Section: Word Learning: Not Just For Childrenmentioning
confidence: 99%
“…But with collaborators Ping Li and Aneta Pavlenko, we found that even with later second‐language learning, first‐language word use can be influenced by the second language (Malt & Lebkuecher, 2017; Malt, Li, Pavlenko, Zhu, & Ameel, 2015; Pavlenko & Malt, 2011). A number of variables influence where the two languages interact and what the outcomes are (e.g., Malt, 2019c; Malt, Yang, & Joseph, 2021; Pavlenko & Malt, 2011; Zinszer, Malt, Ameel, & Li, 2014). The findings underscore the dynamic nature of the lexical networks, adding to a growing understanding of the flexibility of language representations extending well beyond the early learning years.…”
Section: Word Learning: Not Just For Childrenmentioning
confidence: 99%